MENUMBUHKAN MINAT MEMBACA DAN MENULIS BAHASA INDONESIA DIKALANGAN ANAK REMAJA - Davina Indah Zarani; Meilan Arsanti (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The factors that influence the literacy of the younger generation are very complex and require language skills and innovative thinking. Reading and writing at a young age has an important role in the development of existing fonts and influences the speed of reading and writing skills. Society must understand the importance of reading from an early age to improve writing skills and have significant implications in individual life and society.